Empirical investigation on determinants of loan repayment intention among households in Melaka, Malaysia / Nur Artika Mahat - Mahat, Nur Artika (Faculty of Business and Management, 2019)
The highlighted issue from this research is low intention to repay loan among household in Melaka, Malaysia. Low loan repayment intention can lead to default payment, delinquency as well as bankruptcy. This research is to investigate the relationships between financial attitude, financial literacy and financial socialization with loan repayment intention. The respondents in this research is households in Melaka, Malaysia which involved totals of 257 working at Universiti Teknologi MARA (UiTM) Kampus Bandaraya, Amanah Saham Nasional Berhad (ASNB), SH Motors Sdn Bhd and Seri Negeri Melaka. The sampling chosen in this research is purposive sampling. By using the Statistical Package for the Social Science (SPSS) version 22, all data gathered were analyzed. In order to obtain the result, frequency distribution, descriptive analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis were conducted in the analysis part. The research used Social learning theory and theory of planned behavior to propose the theoretical framework. The research investigates the relationship of financial attitude, financial literacy and financial socialization with loan repayment intention among household in Melaka. Thus, in this research findings found that financial attitude has a significant relationship between with loan repayment intention. These finding could contribute to the body of knowledge by identifying determinants of loan repayment intention among households in Melaka.